Toxicity of glyphosate herbicides formulated for Africanized Apis mellifera Linnaeus, 1758 (Hymenoptera: Apidae) - Lucas Battisti; Michele Potrich; Raiza Abati; Amanda Roberta Sampaio; Gabriela Libardoni; Fabiana Martins Costa-Maia; Elizabete Artus Berté; Claudia Bueno dos Reis Martinez; Silvia Helena Sofia (Ecotoxicology and Environmental Safety)
Initially, products based on glyphosate (GLY) were considered non-toxic or slightly toxic to bees. Still, recent research has shown that these products can cause mortality or trigger sublethal effects in these insects. Roundup Transorb R® (RT) is one of the GLY-based formulations sold in Brazil. It is used in several crops, and studies are required on its toxicity to honey bees. Thus, the objective of this work was to evaluate, under laboratory conditions, the lethal and sublethal effects of RT for adult workers (foragers) of Africanized A. mellifera. For this, two bioassays were carried out with Africanized honey bees. The experimental design was completely randomized, consisting of five treatments (T0 - control, T25 – 25 % GLY, T50 – 50 % GLY, T75 – 75 % GLY, and T100 GLY – 100 % recommended dose). The bioassays were carried out as follows: (1) Acute oral and topical exposure, evaluating mortality, effects on flight capacity, vertical displacement, and locomotion (in the latter only for oral contamination), consisting of five repetitions and 10 honey bees per repetition; (2) Chronic exposure via the oral route and spraying, assessing mortality, for both contamination routes and damage to the midgut epithelium thickness when contaminated via the oral route, composed of five replicates and 20 honey bees per replicate. The results showed that chronic oral exposure to RT can increase honeybee mortality and damage the thickness of their midgut epithelium. In addition, when acutely exposed orally, the honey bees had reduced walking ability. RT did not affect the other evaluated parameters. Thus, it is concluded that the RT-formulated GLY can affect the survival, midgut morphology, and behavior of A. mellifera.